Manganese in Plants: From Acquisition to Subcellular Allocation - Alejandro, Santiago; Höller, Stefanie; Meier, Bastian; Peiter, Edgar (Frontiers in plant science, 2020)
Manganese (Mn) is an important micronutrient for plant growth and development and sustains metabolic roles within different plant cell compartments. The metal is an essential cofactor for the oxygen-evolving complex (OEC) of the photosynthetic machinery, catalyzing the water-splitting reaction in photosystem II (PSII). Despite the importance of Mn for photosynthesis and other processes, the physiological relevance of Mn uptake and compartmentation in plants has been underrated. The subcellular Mn homeostasis to maintain compartmented Mn-dependent metabolic processes like glycosylation, ROS scavenging, and photosynthesis is mediated by a multitude of transport proteins from diverse gene families. However, Mn homeostasis may be disturbed under suboptimal or excessive Mn availability. Mn deficiency is a serious, widespread plant nutritional disorder in dry, well-aerated and calcareous soils, as well as in soils containing high amounts of organic matter, where bio-availability of Mn can decrease far below the level that is required for normal plant growth. By contrast, Mn toxicity occurs on poorly drained and acidic soils in which high amounts of Mn are rendered available. Consequently, plants have evolved mechanisms to tightly regulate Mn uptake, trafficking, and storage. This review provides a comprehensive overview, with a focus on recent advances, on the multiple functions of transporters involved in Mn homeostasis, as well as their regulatory mechanisms in the plant's response to different conditions of Mn availability.